Synergy Between Civic Education And Pancasila Values In Fostering Human Rights Awareness In The Era Of Globalisation - Handoyo, Cecilia Chelsea Widia; Mutiarani, Miladya; Setiawan, Naailah Ranaa; Anandhita, Shelsy Trista (Media Hukum Indonesia (MHI), 2026)
The wave of globalization and advances in information technology has brought about a sea change affecting the way people live, relate to one another and behave/ particularly, young people. While on one side, globalisation has brought about open access to information and universal values, at the other it has presented us with challenges that include intolerance, discrimination and a waning consciousness of human rights. It demonstrates that the concepts of human rights have not gone deep down into society. It is, therefore, imperative to reinforce meaningful and sustainable values education. Indeed, civic education has a vital function in the formation of democratic, critical and responsible citizens. In the meantime Pancasila as state ideology also has the values of humanity, justice, unity and respect for human dignity that are consistent with human rights principles. This research focuses on the synergy between Civic Education and Pancasila values to create awareness of human rights in the globalisation era. The reserach uses descriptive qualitataive method with literature review model. Materials: Sources of data were scanned from books, journals and relevant academic materials. The study findings prove that the implantation of Pancasila values in Civic Education learning can extend the awareness of human right in contextual and national ideology perspective. This convergence contributes to a concept of human rights that is not only theoretical but deals with its application in social life.